Comparison Between Primary and Secondary Method of Closing Surgical Wound After Tooth Extraction: A Split-Mouth Study - Vipin Aggarwal; Meenaxi Umarani; Shridhar D. Baliga; Rakhi Issrani; Namdeo Prabhu (Association of Support to Oral Health Research (APESB), 2021)
Objective: To compare and assess the primary and secondary closure techniques following extraction of impacted third molars for post-operative complications. Material and Methods: In total, 30 patients ranging between 18-30 years of age and of either sex who had bilaterally impacted mandibular third molars were randomly selected. Split mouth study method was used so that the participants served as their own control. Group 1 consisted of primary closure of left mandibular impacted third molars and Group 2 consisted of secondary closure of right mandibular impacted third molars. Basement evaluations were recorded for each patient along with subjective and objective evaluations for postoperative 7 days. Data analysis was carried out by SPSS 17.0 software using Mann-Whitney U test, Wilcoxon matched-pairs test and t-test. A p-value ≤ 0.05 was assigned as statistically significant. Results: When compared to group 1, group 2 revealed statistically less pain and swelling following the secondary closure of wound from day 1 to 7. There was a significant improvement in mouth opening in Group 2 at day 1 (p=0.0005) and at day 7 (p=0.00001). Conclusion: Secondary wound closure after disimpaction of mandibular third molar results in better postoperative recovery than primary closure.